Pengaruh Penyaluran Dana Zakat, INFAK & Sedekah (ZIS), Produk Domestik Regional Bruto (PDRB) & Angka Pengangguran Terbuka Terhadap Kemiskinan - Luthfiyah Luthfiyah; Dewi Riza Lisvi Vahlevi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Poverty is one of the most difficult economic problems to solve. This problem occurs in all countries. Among the causes of poverty are poor human resources, a low quality of life, a rising unemployment rate, and a decrease in job availability each year, as well as wages that do not match living costs. This is not only due to low human resources; the government also plays a crucial role in this issue. The poverty rate is unavoidable, so an appropriate solution is needed to address this issue. One step to reducing poverty is to analyze which economic instruments can be optimized, especially in the Sidoarjo region. The poverty rate in Sidoarjo is quite high. The open unemployment rate in Sidoarjo ranks third in East Java province. Therefore, the author was interested in conducting this research. This study aims to determine the effect of the distribution of zakat, infaq, and alms (ZIS) funds, GRDP, and open unemployment on the poverty rate in Sidoarjo in 2013-2023. This study uses a quantitative method with multiple linear regression analysis. The data processing tool used is SPSS. The results of the T test indicate that the distribution of ZIS funds has a significant effect on the poverty rate, while GRDP and open unemployment do not have a significant effect on the poverty rate partially. The F test shows that the distribution of ZIS funds, inflation, and GDP have a significant effect on the poverty rate simultaneously in the period 2013-2023. The limitation of this study is the use of variables that affect the poverty rate, so that future researchers can add or change these variables with other variables related to poverty.